REVOLUSI KEPEMIMPINAN PENDIDIKAN: TRANSFORMASI DARI ERA TRADISIONAL MENUJU ERA DIGITAL - Siswadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The transformation of education in the digital era requires a fundamental shift in educational leadership paradigms. This study aims to analyze the revolution of educational leadership from the traditional era to the digital era and its implications for modern education systems. This research employs a qualitative approach using a literature review method, drawing on books, academic journals, and relevant documents. The findings indicate that technological advancements have significantly transformed learning processes, including improved accessibility, flexibility, and technology-based personalized learning. Furthermore, educational leadership has evolved from an authoritarian model (Leadership 1.0) to a human-centered approach (Leadership 5.0), emphasizing collaboration, innovation, adaptability, and empathy. This transformation also presents challenges such as the digital divide, data security issues, and the readiness of human resources. However, it offers substantial opportunities, including the integration of artificial intelligence and the development of 21st-century skills to enhance educational quality. Therefore, adaptive leadership plays a crucial role in managing change and ensuring the successful transformation of education in the digital era.